"Radical Spirits": Spiritualism and Women's Rights in Nineteenth Century America - Cook, Ramsay (Labour / Le Travail, 1991)
The article reviews the book, "'Radical Spirits': Spiritualism and Women's Rights in Nineteenth Century America," by Ann Braude.
Keywords: BOOKS – Reviews; BRAUDE; Ann; Nonfiction; RADICAL Spirits: Spiritualism & Women's Rights in Nineteenth-Century America (Book); Women's rights